Pengaruh Kompetensi, Independensi, Profesionalisme dan Tekanan Anggaran Waktu terhadap Kualitas Audit Aparat Inspektorat dengan Pengalaman sebagai Variabel Moderatıng - Pirmansyah, Pirmansyah; Hasan, Amir; Andreas, Andreas (Jurnal Ekonomi, 2019)
This study aims to prove the influence of Competence, Independence, Professionalism and Time Budget Pressure Apparatus on the Audit Quality Inspectorate Apparatus with Experience as moderating variables. This type of research done on the inspectorate in Kampar. This study is a survey research using census method, whereas the spreading technique using a questionnaire distributed to inspectors of the Inspectorate, population in this study is the auditor who works at the office inspectorate, a questionnaire distributed 44, a total of 39 questionnaires were returned. Data was analyzed using multiple linear regression testing and MRA. The value of the partial test or t test each independent variable on the dependent variable obtained results that the partial competence, professionalism and Time Budget Pressure effect on audit quality, while independence has no effect on audit quality. The experience also proved unable to affect the relationship of competence, independence, professionalism and budget pressure on audit quality. The results shows that which R2 of 0.571 where it explains that the percentage of donated influence of independent variables (Competence, Independence, Professionalism and Time Budget Pressure) on dependent variable (auditquality) of 57.1% while the remaining 42.9% influenced by other variables not included in this research.